Neurological Manifestations in Peri-Partum Period: Imaging Overview - Ranjan, Rahul; Gupta, Aman; Deo , Namrata; Pandey, Nirmal; Singh, Anil; Varshney, Sumedha (Nepal Journal of Neuroscience, 2025)
The peripartum period, covering late pregnancy through postpartum, brings significant changes that increase the risk of neurological disorders such as cortical vein thrombosis (CVT), osmotic demyelination syndrome (ODS), pituitary apoplexy, postpartum cerebral angiopathy (PCA), posterior reversible encephalopathy syndrome (PRES), and intracranial hypotension (IH). Accurate diagnosis relies heavily on MRI and CT, with MRI being especially useful for its detailed images. CVT often presents with severe headaches and seizures, detected on MRI through characteristic signs like the “empty delta sign.” ODS, linked to the rapid correction of low sodium levels, appears as T2 hyperintense lesions at specific locations. Pituitary apoplexy, involving sudden hemorrhage within a pituitary adenoma, typically requires high-dose corticosteroids and, in severe cases, surgery. PCA results from hormonal changes and shows as transient artery narrowing on MR angiography, managed with supportive care. PRES, associated with high blood pressure disorders, manifests as vasogenic brain edema, treated by managing blood pressure. IH, often seen after a dural puncture, leads to positional headaches and shows brain sagging on MRI, with treatments ranging from rest to epidural blood patches. Recognizing these imaging patterns is critical for timely diagnosis and effective treatment, ultimately enhancing outcomes for mothers & preventing peripartum morbidity & mortality.